Estimating the age of p.(Phe508del) with family studies of geographically distinct European populations and the early spread of cystic fibrosis. (December 2018) - Farrell, Philip; Férec, Claude; Macek, Milan; Frischer, Thomas; Renner, Sabine; Riss, Katharina; Barton, David; Repetto, Teresa; Tzetis, Maria; Giteau, Karine; Duno, Morten; Rogers, Melissa; et al.
Abstract The high incidence of cystic fibrosis (CF) is due to the frequency of the c.1521_1523delCTT variant in the cystic fibrosis transmembrane conductance regulator (CFTR ), but its age and origin are uncertain. This gap limits attempts to shed light on the presumed heterozygote selective advantage that accounts for the variant's high prevalence among Caucasian Europeans and Europe-derived populations. In addition, explaining the nature of heterozygosity to screened individuals with one c.1521_1523delCTT variant is challenging when families raise questions about these issues. To address this gap, we obtained DNA samples from 190 patients bearing c.1521_1523delCTT and their parents residing in geographically distinct European populations plus a Germany-derived population in the USA. We identified microsatellites spanningCFTR and reconstructed haplotypes at 10 loci to estimate the time/age of the most recent common ancestor (tMRCA) with theEstiage program. We found that the age estimates differ between northwestern populations, where the mean tMRCA values vary between 4600 and 4725 years, and the southeastern populations where c.1521_1523delCTT seems to have been introduced only about 1000 years ago. The tMRCA values of Central Europeans were intermediate. Thus, our data resolve a controversy by establishing an early Bronze Age origin of the c.1521_1523delCTT allele and demonstrating its likely spread from northwest to southeast during ancient migrations. Moreover, taking the archeological record into account, our results introduce a novel concept by suggesting that Bell Beaker folk were the probable migrating population responsible for the early dissemination of c.1521_1523delCTT in prehistoric Europe.